"Evaluación de diferentes concentraciones para obtener néctar de piña (Ananas comosus) enriquecido con hojas de chaya (Cnidoscolus chayamansa) en la provincia de los Ríos cantón Quevedo" - Álvarez Meza, José Luis (2012)
As ourpredominalty agricultural cuntry, yet coul no find a definitivi answer to meet the constant demand for products used as raw material for the food industry, and can meet needs of humans. The pineapple )Ananas comosus) occurs throughout the year and is very desired by the vast majority oh people who know their characteristics, for their great taste and distintive aroma, being one of the healthies fruist of all, has a good source of fiber, is rich in vitamin C and is low in calories.......................................